Revitalization of Kalosara Value as a Model of Conflict Resolution Based on Local Wisdom in Tolaki Wolasi Community - Ikhsan, Muh; Alifuddin, Muh; Sabri, Muhammad; Sodiman, Sodiman; Danial, Danial (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The ideological conflict that occurred between the Aoma and Ambesakoa communities can be managed creatively and wisely through Kalosara (a symbol of Tolaki customs that emphasizes unity). This is based on efforts to respect each other and maintain harmony based on Tolaki awareness, a culture rooted in the Kalosara concept. Previous research has widely reviewed Kalosara as a symbol of Tolaki customs. However, an in-depth study of its role as a step to resolve conflicts based on local wisdom has not been updated, so this study aims to analyze the revitalization of Kalosara values as a model for conflict resolution. The setting of this research is in Wolasi, South Konawe Regency, involving various informants including the South Konawe Regency government, the South Konawe Regency Ministry of Religion, customary observers, and the local community. The Participatory Action Research method was used to examine data in a participatory manner by researchers. The results of this study found that Kalosara is a conflict resolution model based on the local wisdom of the Wolasi community, Tolaki Tribe, which paves the way for consensus in the form of socio-cultural integration in society in a segregated atmosphere, with the value of medulu mepoko'aso (unity and oneness), ate pute penao moroha (sanctity and justice), and morini mbu'umbundi monapa mbu'u ndawaro (prosperity and welfare). Through this study, implications for conflict resolution based on local wisdom were obtained, including the stages of presenting Kalosara (a sacred symbol of peace), an oath or joint statement about the promise of peace, an attitude of accepting customary decisions, and reconciliation or parties in conflict.